Effect of High Frequency Heating Time on Glue Bond Quality in Laminated Rubberwood - Md. Tahir, Helmi (1991)
About 70% of Malaysia's furniture are made from Rubberwood. Most of the rubberwood used in this industry are in the form of laminated boards. One of the critical factors in the production line of wood lamination is the curing time of the glue line. One way to overcome the time consumption is by using High Frequency curing method. This study is aimed to determine and to assess the performance of glue bond quality under different heating times using wood at various grain patterns. Polyvinyl acetate (PVAc) plus a hardener was used as the bonding agent. The boards were subjected to 10 heating times, starting from 1.5 minutes with an increment of 1 minute. The glued boards were of 4 types of grain pattern; radial -radial faces, radial-tangential faces, tangential -tangential faces and bastard sawn. Thirty samples were prepared for each grain pattern arrangement at each heating time and were subjected to shear block test. The shear results obtained were statically analyzed using analysis of variance. It was found that the 1.5 minutes curing time was sufficient to produce the necessary glued bond quality. This heating time produces results that satisfy the requirements of Japan Agricultural Standard . The requirements called for bond quality with a minimum of 60kgf/cm² and 60 % wood failure when subjected to block shear test, and the ratio of delamination must not exceed 1/3 of the total length. The results also indicated that a s early as 1.5 minutes, the glue line temperature had achieved 100˚C which is the minimum temperature required to cure the adhesive . The adhesive used is found to be highly moisture resistant since none of the samples delaminated during the cold water soak test. No significant difference was found among the position eventhough the middle position gave the highest shear strength. Tangential - tangential faces has the highest shear strength, however, when compared to bastard sawn lamination, it was not significantly different. By comparing heating time, it shows that 1.5 minutes has the highest shear strength and wood failure (139.80 kgf/cm, 95% respectively), which is highly significant compared to the other heating times